THE LESSONS OF THE WORLD CRISIS AND THEIR REFLECTION IN ANTI-CRISIS PROGRAMS OF RUSSIA AND CIS COUNTRIES - Tatarkin, Aleksander; Tatarkin, Denis (Вісник Економіки, 2017)
This paper analyzes causes and consequences of the world crisis, its systematic and permanent character is shown. The essence of the crisis and its characteristics in different countries and areas is reviewed. Projections and consequences for the Russian economy and the global community are made and estimated. Theoretical, methodological and practical advices on the formation of anti-crisis measures are formulated. The priority measures of conservation and expanded reproduction of the population and real economy support through balanced economic, social and pricing policies for the Russian Federation are substantiated.